FRS7 and FRS12 recruit NINJA to regulate expression of glucosinolate biosynthesis genes. Issue 4 (14th May 2020) - Fernández‐Calvo, Patricia; Iñigo, Sabrina; Glauser, Gaétan; Vanden Bossche, Robin; Tang, Michelle; Li, Baohua; De Clercq, Rebecca; Nagels Durand, Astrid; Eeckhout, Dominique; Gevaert, Kris; De Jaeger, Geert; Brady, Siobhan M.; et al.
Summary: The sessile lifestyle of plants requires accurate physiology adjustments to be able to thrive in a changing environment. Plants integrate environmental timing signals to control developmental and stress responses. Here, we identified Far1 Related Sequence (FRS) 7 and FRS12, two transcriptional repressors that accumulate in short‐day conditions, as regulators of Arabidopsis glucosinolate (GSL) biosynthesis. Loss of function of FRS7 and FRS12 results in plants with increased amplitudes of diurnal expression of GSL pathway genes. Protein interaction analyses revealed that FRS7 and FRS12 recruit the NOVEL INTERACTOR OF JAZ (NINJA) to assemble a transcriptional repressor complex. Genetic and molecular evidence demonstrated that FRS7, FRS12 and NINJA jointly regulate the expression of GSL biosynthetic genes, and thus constitute a molecular mechanism that modulates specialized metabolite accumulation.